2021
DOI: 10.3390/biology10080721
|View full text |Cite
|
Sign up to set email alerts
|

Light Quality-Dependent Regulation of Non-Photochemical Quenching in Tomato Plants

Abstract: Photosynthetic pigments of plants capture light as a source of energy for photosynthesis. However, the amount of energy absorbed often exceeds its utilization, thus causing damage to the photosynthetic apparatus. Plants possess several mechanisms to minimize such risks, including non-photochemical quenching (NPQ), which allows them to dissipate excess excitation energy in the form of harmless heat. However, under non-stressful conditions in indoor farming, it would be favorable to restrict the NPQ activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
6
8
0
Order By: Relevance
“…However, it is still unclear how different light qualities affect T leaf . Such a response, however, was expected, based on the results of previous studies [3,12], and we found that stomatal conductance and NPQ are related to the lighting spectra applied during plant growth in controlled-environment agriculture. It was noticed that the progressive replacement of R light by G light in the growth RB spectrum decreases stomatal dimensions, thus reducing g s and E and, consequently, improving water-use efficiency [12] while decreasing evaporative cooling and presumably increasing foliar temperature [11].…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…However, it is still unclear how different light qualities affect T leaf . Such a response, however, was expected, based on the results of previous studies [3,12], and we found that stomatal conductance and NPQ are related to the lighting spectra applied during plant growth in controlled-environment agriculture. It was noticed that the progressive replacement of R light by G light in the growth RB spectrum decreases stomatal dimensions, thus reducing g s and E and, consequently, improving water-use efficiency [12] while decreasing evaporative cooling and presumably increasing foliar temperature [11].…”
Section: Introductionsupporting
confidence: 50%
“…Moreover, the examined NPQ value in tomato plants grown under monochromatic (R, G, or B) or mixed RGB (1:1:1) light confirmed that R-and B-light treatments enhanced NPQ amplitude, while plants grown under G and RGB spectra presented a significantly lower amplitude of NPQ due to the reduced accumulation of NPQ-related proteins (PsbS, VDE, cytf, and PGRL1) [3]. Another study [15] documented that NPQ amplitude increased in tomato plants grown under RB-and monochromatic B-light spectra compared to values noted under white light with G-light (544 nm) peak wavelength.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The replacement of R light with a G in growth spectrum significantly reduced the excitation pressure on PSII and Φ NPQ , and improved the rate of electron transport. Liu et al ( 2017 ) suggested that the addition of G light to the spectrum affects the subsequent light absorption utilized for photosynthesis, whilst Trojak and Skowron ( 2021 ) showed that tomato plants grown under monochromatic G or mixed RGB light presented a decreased NPQ rate, as compared to monochromatic red or blue light. Additionally, Yousef et al ( 2021 ) showed that the best performance of the photosynthetic apparatus was observed under a mixture of R and B light (R7: B3) or a mixture of R, G and B light (R3: G2: B5).…”
Section: Discussionmentioning
confidence: 99%
“…During evolution on terrestrial habitats, the algal ancestors of extant land plants had to adjust to a broad range of new environmental stimuli and abiotic stresses. Besides the evolution of waterconducting tissues and strategies for desiccation tolerance, land plants had to adapt to the exposure to high sun light intensities (Trojak & Skowron, 2017). While sun light provides photosynthetic energy and important cues for plant growth, high-intensity sun light damages the photosynthetic machinery and has detrimental effects on plant survival (Demmig-Adams & Adams, 1992).…”
Section: Introductionmentioning
confidence: 99%